Quorum–based location service protocol for vehicular ad hoc networks in urban environment. (9th September 2013) - Zaki, Salim M.; Ngadi, M.A.; Kamat, Maznah; Razak, Shukor Abd
The existing location service protocols used in vehicular ad hoc network (VANET) environments suffer from poor scalability, and do not consider load distribution on location servers while the usage of unrealistic information for selecting location servers affects the efficiency of the protocols. This paper presents a vehicular quorum location service (VQLS) protocol, which is designed for an urban area topology. VQLS uses fuzzy inference engine (FIE) in selecting the most stable node to be a main location server (MLS) based on the distance of a node to intersection centre point and its speed. The server constructs a quorum group, which consists of the nominated nodes that passing through the intersection in order to distribute the load on quorum members. VQLS shows superior performance in reducing overhead of control packets, and balance the load on dense intersection vicinity. Additional achievement is low end–to–end delay for routing packets.